Civil society as a model of relations between human and the state: from history to modernity - Череватюк, Вікторія Богданівна; Олексієнко, Юлія Євгеніївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article theoretically substantiates the main stages of civil society’s increasing and development, and its features. Also the authors characterize current state of the civil society in Ukraine and determine the basic direction of improvement of interaction of the state and civil society.